Penebusan Dosa dalam Kekristenan: Analisis Teks Suci Bible (Departement of Comparative Study of Religions, 2023)
Sin has been a frequently discussed topic in the context of Christianity. The concept of inherited sin is viewed as a barrier between humans and God. Christians believe in the redemption of this sin through the sacred blood of Jesus Christ. This concept was prophesied in the Old Testament and fulfilled in the New Testament. This research focuses on the fundamental question regarding the forgiveness of sins through the blood of Jesus, which, over time, evolved from the practice of redemption through priests to the inclusion of indulgences. The objective of this study is to examine and comprehend the sacredness of Jesus Christ's blood, which is the centerpiece of Christian belief, where His blood is seen as the means of sin redemption. A critical descriptive analysis method is employed to explore these the means of sin redemption. A critical descriptive analysis method is employed to explore these viewpoints, revealing various dilemmas arising from Paul's interpretation of this concept. The research findings indicate that the concept of sin in Christianity is a core element of Christian faith, wherein inherited sin can only be absolved through the sacrificial blood of Jesus. However, contemporary Christian teachings have undergone transformations that alter original aspects of the doctrine, where Paul's interpretations, seen as introductions to Christian teachings, influence the original meanings and give rise to the practice of indulgences, which have become part of the evolving Christian doctrine.